Sanksi Pidana terhadap Pelaku Tindak Pidana Penggelapan dalam Situs Jual Beli Online - Made Rony Setiawan; A.A. Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2020)
Nowadays in the world of electronic transactions many deviant acts are found, and are not based on existing legal norms, which mostly occur in the online trading system. Online sales and purchases are sometimes only based on trust, which means that the perpetrators of trade are sometimes unclear. Thus, this study was conducted to determine the legal arrangements regarding the actions that have been carried out by business actors to consumers and criminal sanctions imposed on perpetrators of embezzlement in online trading sites. This study uses a normative method because there are still vague norms, based on the opinions of legal scholars and the Law. Prohibition of business actors in marketing activities is regulated in Article 9 paragraph 1 of the Consumer Protection Act prohibiting business actors from offering, promoting, advertising goods and / or services incorrectly or as if the goods have fulfilled and have discounted prices, special prices , certain quality standards, certain styles or modes, certain characteristics, certain history or uses, the goods are in good or new condition, the goods and services have been obtained or have a sponsor, approval, certain equipment, certain benefits. Crimes of embezzlement are based on the provisions of article 372 KUHP, which means that someone who has someone's belongings with the intention of violating the law is an embezzlement.